Hadith #2270 - Sunan Abi Dawud - Amir al-Sha'bi عامر الشعبي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Salma ibn al-Akwa; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
Three persons were brought to Ali (Allah be pleased with him) when he was in the Yemen. They and sexual intercourse with a woman during a single state of purity. He asked two of them: Do you acknowledge this child for this (man)? They replied: No. He then put this (question) to all of them. Whenever he asked two of them, they replied in the negative. He, therefore, cast a lot among them, and attributed the child to the one who received the lot. He imposed two-third of the blood-money (i.e. the p
Grade: Sahih

Hadith #2311 - Sunan Abi Dawud - Ma'tmar bin Sulaiman-al-Taufayl معتمر بن سليمان - الطفيل; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
Musaykah, a slave-girl of some Ansari, came and said: My master forces me to commit fornication. Thereupon the following verse was revealed: “But force not your maids to prostitution (when they desire chastity).”
Grade: Sahih

Hadith #2332 - Sunan Abi Dawud - Ash'uth bin Qays; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
That Umm al-Fadl, daughter of al-Harith, sent him to Mu’aqiyah in Syria. He said: I came to syria and performed her work. The moon of Ramadan appeared while I was in Syria. We sighted the moon on the night of Friday. When I came to Median towards the end of the month (of Ramadan), Ibn ‘Abbas asked me about the moon. He said: When did you sight the moon ? I said: I sighted it on the night of Friday. He asked: Did you sight it yourself ? I said: Yes, and the people sighted it. They fasted and
Grade: Sahih

Hadith #2619 - Sunan Abi Dawud - Ja'far bin Iyas; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
The Prophet (ﷺ) said: When one of you comes to the cattle, he should seek permission of their master if he is there; if he permits, he should milk (the animals) and drink. If he is not there, he should call three times. If he responds, he should seek his permission; otherwise, he may milk (the animals) and drink, but should not carry (with him).
Grade: Sahih

Hadith #2790 - Sunan Abi Dawud - Amr bin Muslim al-Jndy عمرو بن مسلم الجندي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
I saw Ali sacrificing two rams; so I asked him: What is this? He replied. The Messenger of Allah (ﷺ) enjoined upon me to sacrifice on his behalf, so that is what I am doing.
Grade: Da'if

Hadith #3177 - Sunan Abi Dawud - Jabir bin Samra; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
An animal was brought to the Messenger of Allah (ﷺ) while he was going with a funeral. He refused to ride on it. When the funeral was away, the animal was brought to him and he rode on it. He was asked about it. He said: The angels were on their feet. I was not to ride while they were walking. When they went away, I rode.
Grade: Sahih

Hadith #3210 - Sunan Abi Dawud - Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
That ‘Abd al-Rahman b. ‘Awf alighted in the grave of the Prophet (ﷺ). He said: I still seem to see the four of them.
Grade: Sahih

Hadith #3247 - Sunan Abi Dawud - Abu Hurairah; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Ibn Sirin محمد بن سيرين الأنصاري; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: If anyone swears on oath is the course which he says: “By al-Lat” he should say: There is no god but Allah, and that if anyone says to his friend: Come and let me play for money with you, he should give something in charity (sadaqah).
Grade: Sahih

Hadith #3335 - Sunan Abi Dawud - Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Suwayd bin Qays al-Tajibi سويد بن قيس التجيبي; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
I heard Messenger of Allah (ﷺ) say: Swearing produces a ready sale for a commodity but blots out the blessing. The narrator Ibn al-Sarh said: “for earning”. He also narrated this tradition from Sa’id b. al-Musayyab on the authority of Abu Hurairah from the Prophet (ﷺ).
Grade: Sahih

Hadith #3387 - Sunan Abi Dawud - Abu 'Ubaidah ibn al-Jarrah; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; ibn Mas'ud; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: If any of you can become like the man who had a faraq of rice, he should become like him. They (the people) asked: Who is the man who had a faraq of rice with him, Messenger of Allah ? Thereupon he narrated the story of the cave when a hillock fell on them (three persons), each of them said: Mention any best work of yours. The narrator said: The third of them said: O Allah, you know that I took a hireling for a faraq of rice. When the evening came, I pre
Grade: Hasan

Hadith #3419 - Sunan Abi Dawud - Abdullah bin Abi al-Safar عبد الله بن أبي السفر; Amir al-Sha'bi عامر الشعبي; Kharjh bin al-Slt al-Brjmy خارجة بن الصلت البرجمي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
This tradition has also been transmitted by Abu Sa’id al-Khudri form the Prophet (ﷺ).
Grade: Sahih

Hadith #3424 - Sunan Abi Dawud - Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Abu Hurairah; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin Jahada محمد بن جحادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
That Abu Tibah cupped the Messenger of Allah (ﷺ) and he ordered that a sa’ of dates be given to him, also ordering his people to remit some of his dues.
Grade: Sahih

Hadith #3475 - Sunan Abi Dawud - Kahmas bin al-Hasan al-Tamimi كهمس بن الحسن التميمي; Manzur bin Siyar al-Fazari منظور بن سيار; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Siyar bin Manzur bin Siyar سيار بن منظور بن سيار; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
“He used: ‘Not purify them ; grievously will be their penalty.'” He said about (selling) the goods: I swear by Allah, I was given (the price) so and so for it. The other man considered it to be correct and bought it.
Grade: Sahih

Hadith #3896 - Sunan Abi Dawud - Abdullah bin Abi al-Safar عبد الله بن أبي السفر; Amir al-Sha'bi عامر الشعبي; Kharjh bin al-Slt al-Brjmy خارجة بن الصلت البرجمي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin Bashar Bindar محمد بن بشار بندار; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
Alaqah came to the Messenger of Allah (ﷺ) and embraced Islam. He then came back from him and passed some people who had a lunatic fettered in chains. His people said: We are told that your companion has brought some good. Have you something with which you can cure him? I then recited Surat al-Fatihah and he was cured. They gave me one hundred sheep. I then came to the Messenger of Allah (ﷺ) and informed him of it. He asked: Is it only this? The narrator, Musaddad, said in his other version:
Grade: Sahih

Hadith #3900 - Sunan Abi Dawud - Abdullah bin Abi al-Safar عبد الله بن أبي السفر; Amir al-Sha'bi عامر الشعبي; Kharjh bin al-Slt al-Brjmy خارجة بن الصلت البرجمي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
Some of the Companions of the Prophet (ﷺ) went on a journey. They alighted with a certain clan of the Arabs. Someone of them said : Our chief has been stung by a scorpion or bitten by a snake. Has any of you something which gives relief to our chief? A man of the people said : Yes, I swear by Allah. I shall apply charm ; but we asked you for hospitality and you denied it to us. I shall not apply charm until you give me some payment. So they promised to give some sheep to him. He came to him an
Grade: Sahih

Hadith #4096 - Sunan Abi Dawud - ibn Abbas; Ikrama عكرمة; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
Why do you put on the lower garment in this way? He replied: It is how I saw the Messenger of Allah (ﷺ) do it.
Grade: Sahih

Hadith #4329 - Sunan Abi Dawud - Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin al-Munkdar bin 'Abdullah محمد بن المنكدر بن عبد الله بن الهدير; Sa'd bin Ibrahim سعد بن إبراهيم بن عبد الرحمن; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
The prophet (ﷺ) passed by Ibn Sa’Id along with some of his companions. ‘Umar b. al-Kattab was among them. He was playing with boys near the fortress of Banu Maghalah. He was near the age of puberty (i.e. a boy). Before he was aware, the Messenger of Allah (ﷺ) gave him a pat on the back and said : Do you testify that you are the Messenger of Allah Ibn Sayyad then looked at him and said: I testify that you are the Apostle of Gentiles. Ibn Sayyad then said the prophet (ﷺ) then asked him
Grade: Sahih

Hadith #4332 - Sunan Abi Dawud - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
We saw the last of Ibn Sayyad at the battle of the Harrah.
Grade: Sahih

Hadith #4355 - Sunan Abi Dawud - Abdur Rahman bin 'Abdullah bin 'Utba عبد الرحمن بن عبد الله بن عتبة المسعودي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
AbuMusa said: Mu’adh came to me when I was in the Yemen. A man who was Jew embraced Islam and then retreated from Islam. When Mu’adh came, he said: I will not come down from my mount until he is killed. He was then killed. One of them said: He was asked to repent before that.
Grade: Sahih

Hadith #4556 - Sunan Abi Dawud - ibn Abbas; Ikrama عكرمة; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Nasr bin 'Ali bin Nasr bin 'Ali; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان; Yazid bin Zari' يزيد بن زريع (Sunan Abi Dawud)
The Prophet (ﷺ) said: The fingers are equal: ten camels for each finger.
Grade: Sahih

Hadith #4693 - Sunan Abi Dawud - Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Kahmas bin al-Hasan al-Tamimi كهمس بن الحسن التميمي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Yahya bin Y'amar يحيى بن يعمر (Sunan Abi Dawud)
Allah created Adam from a handful which he took from the whole of the earth ; so the children of Adam are in accordance with the earth : some red, some white, some black, some a mixture, also smooth and rough, bad and good.
Grade: Sahih

Hadith #4729 - Sunan Abi Dawud - Hammad bin Zayd حماد بن زيد بن درهم الأزدي الأزرق; Mas'ud bin Malik Abu Razayn al-Asadi مسعود بن مالك أبو رزين الأسدي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Musa bin Isma'il al-Munqari al-Tabudhaki موسى بن إسماعيل المنقري - لتبوذكي; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر; Waki' bin al-Jarrah وكيع بن الجراح; Ya'la bin 'Ata' يعلى بن عطاء العامري (Sunan Abi Dawud)
When we are were sitting with the Messenger of Allah (May peace be upon him) he looked at the moon on the night when it was full, that is, fourteenth, and said : You will see your Lord as you see this (moon) and have no doubts about seeing him. If, therefore, you can keep from being prevented from prayer before the sun rises and before it sets, do so. He then recited :”Celebrate the praise of your Lord before the rising of the sun and before its setting”.
Grade: Sahih

Hadith #4828 - Sunan Abi Dawud - Abu Musa al-Asha'ari; Anas ibn Malik; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
A man came to the Prophet (ﷺ), another man got up from his place for him, and when he went to sit in it, the Prophet (ﷺ) forbade him. Abu Dawud said: The name of Abu al-Khusaib is Ziyad b. ‘Abd al-Rahman.
Grade: Hasan

Hadith #4896 - Sunan Abi Dawud - Abdullah bin 'Awn bin Artaban عبد الله بن عون بن أرطبان الخزار; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin 'Umar al-Qawariri عبيد الله بن عمر القواريري; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
While the Messenger of Allah (ﷺ) was sitting with some of his companions, a man reviled AbuBakr and insulted him. But AbuBakr remained silent. He insulted him twice, but AbuBakr controlled himself. He insulted him thrice and AbuBakr took revenge on him. Then the Messenger of Allah (ﷺ) got up when AbuBakr took revenge. AbuBakr said: Were you angry with me, Messenger of Allah? The Messenger of Allah (ﷺ) replied: An angel came down from Heaven and he was rejecting what he had said to you. Whe
Grade: Hasan

Hadith #4907 - Sunan Abi Dawud - Aisha bint Abi Bakr; Ata' bin Abi Rabah عطاء بن أبي رباح; Habib al-Ma'lm Abu Muhammad حبيب المعلم أبو محمد البصري; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
I heard the Messenger of Allah (May peace be upon him) say: Men given to cursing will not be witnesses or intercessors.
Grade: Sahih

Hadith #4935 - Sunan Abi Dawud - Aisha bint Abi Bakr; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
When we came to Medina, the women came to me when I was playing on the swing, and my hair were up to my ears. They brought me, prepared me, and decorated me. Then they brought me to the Messenger of Allah (ﷺ) and he took up cohabitation with me, when I was nine.
Grade: Sahih

Hadith #5085 - Sunan Abi Dawud - Abdur Rahman bin 'Abdullah bin 'Utba عبد الرحمن بن عبد الله بن عتبة المسعودي; Abu Dharr al-Ghaffari; al-Qasim ibn Muhammad القاسم بن محمد بن أبي بكر الصديق; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
Shariq al-Hawzani and I came to Aisha (Allah be pleased with her) and asked her: By which (prayer) the Messenger of Allah (ﷺ) began when he woke up at night? She replied: You asked me about a thing which no one asked me before. When he woke up at night, he uttered: “Allah is Most Great” ten times, and uttered “Praise be to Allah” ten times, and said “Glory be to Allah and I begin with His praise” ten times, and said: “Glory be to the King, the Most Holy” ten times, and asked Al
Grade: Hasan Sahih

Hadith #5177 - Sunan Abi Dawud - Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Mua'dh bin Mua'dh bin Nsr معاذ بن معاذ بن نصر; Raba'i bin Harash bin Jahsh ربعي بن حراش; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaidullah bin Mua'dh عبيد الله بن معاذ بن معاذ بن نصر (Sunan Abi Dawud)
A man of Banu Amir told that he asked the Prophet (ﷺ) for permission (to enter the house) when he was in the house, saying: May I enter ? The Prophet (ﷺ) said to his servant: Go out to this (man) and teach him how to ask permission to enter the house, and say to him: “Say : Peace be upon you. May I enter?” The man heard it and said: Peace be upon you! May I enter ? The Prophet (ﷺ) permitted him and he entered.
Grade: Sahih